Community shifts in Segunung Village due to information technology influence - Tripalupi, Merry Fridha; Irawan, Rahmat Edi; Sjuchro, Dian Wardiana; Nurfauziah, Isni (Universitas Padjadjaran, 2023)
Background: The development of information technology has transformed rural communities from their traditional focus on local matters to being integrated into the global society. This shift significantly affects media consumption and production and consequently changes the way people interact with one another as they socialize in both real life and cyberspace. Purpose: This study aimed to find out the communication construction of rural communities living in Carangwulung Village, Wonosalam District, Jombang Regency. Methods: By using a phenomenological approach, the researchers revealed the experiences and meanings of individuals in this phenomenon. In-depth interview was the main data collection technique in this study. Results: The results of the study unveiled a transformative shift in the way rural communities interact and communicate, attributable to the pervasive influence of information technology. Historically, rural communities have been characterized by close-knit bonds, where face-to-face interactions in communal gatherings, festivals, and local meetings were the norm. These events often served as both social and informational hubs, fostering a sense of unity, shared identity, and mutual support. Conclusion: As technology permeates every aspect of life in Segunung traditional village, the shift towards virtual interactions is inevitable, impacting the collective nature of the community. Implications: The presence of the internet changes the communication construction of rural communities where life and community activities become easier by living in a world with real reality and part of cyber society.